Yeast Stress Response and Fermentation Efficiency: How to Survive the Making of Wine - A Review - Bauer, F.F.; Pretorius, I.S. (South African Journal of Enology and Viticulture, 2019)
Fermentation predictability and wine quality are directly dependent on wine yeast attributes that assist in the rapid establishment of numerical dominance in the early phase of wine fermentation, and that determine the ability to conduct an even and efficient fermentation to obtain a desirable alcohol degree. It is therefore not surprising that the primary selection criteria applied to most wine yeast strain development programmes relate to the overall objective of achieving an efficient conversion of grape sugar to alcohol and carbon dioxide, at a controlled rate and without the development of off-flavours. Numerous factors influence the fermentation performance of wine yeast. Following a successful inoculation of grape must with an appropriate starter culture strain, the ability of a wine yeast to adapt to and cope with the hostile environment and stress conditions prevailing in grape juice fermentation are of vital importance to fermentation performance. There is a direct correlation between fermentation efficiency and stress resistance, which refers to the ability of a yeast strain to adapt efficiently to a changing environment and unfavourable growth conditions. Successful yeast cellular adaptation to changes in extracellular parameters during wine fermentation requires the timely perception (sensing) of chemical or physical environmental parameters, followed by accurate transmission of the information to the relevant compartments of the cell. Chemical parameters perceived during wine fermentation include the availability/concentration of certain nutrients (e.g., fermentable sugars, assimilable nitrogen, oxygen, vitamins, minerals, ergosterol and unsaturated fatty acids) and the presence of inhibitory substances (e.g., ethanol, acetic acid, fatty acids, sulfite, phenolic phytoalexins, mycotoxins, bacterial toxins and agrochemical residues). Signals of a physical nature include temperature, pH, agitation and osmotic pressure. The sensing of these environmental signals is carried out by specific receptor proteins, most of them situated on the cellular surface. Once perceived, the information is transmitted by a network of dedicated, interconnected signal transduction pathways to the relevant cellular compartments which implement the adaptive response, a process referred to as "stress response". Intensive research has focused on elucidating the molecular mechanisms involved in stress responses, which are evolutionarily well conserved. Besides furthering our understanding of the fundamental strategies for adaptation to hostile, industrial environments, and the biological resilience of Saccharomyces cerevisiae, the data are of key importance to the future improvement of wine yeast strains. This review describes the different types of stress experienced by wine yeast cells during their life cycles, summarises our current knowledge of some of the most important molecular processes required for the survival of the yeast cell, and highlights the potential benefits for future yeast strain development which can be derived from this research.